Studi Komparatif Kepemimpinan Presiden SBY, Jokowi, dan Prabowo Subianto terhadap Kebijakan Mitigasi AMDAL di Indonesia - Maulana Syikha Firdaus Firdaus (Himpunan Ilmu Hukum dan Ilmu Hukum Islam, 2025)
This study compares Environmental Impact Assessment (EIA/AMDAL) policies during the leadership of SBY, Jokowi, and Prabowo Subianto. A qualitative approach was applied by reviewing regulations, policies, and key cases. Findings show that under SBY, EIA was reinforced through Law No. 32/2009 and forest moratoriums but lacked effective enforcement. Jokowi simplified procedures under the Job Creation Law to boost investment, yet this risked weakening environmental safeguards. Prabowo emphasized institutional strengthening via the BPLH, though practical challenges remain.